Development of an electrochemical sensing platform based on copper oxide - iron oxide composites from malathion - Mopon, Marlon L. Jr
Malathion is an organophosphate used as a pesticide in agricultural production. However, it can potentially lead to environmental and human health issues when present in excess amounts in food and water. In this study, a non-enzymatic electrochemical sensing platform for malathion based on CuO/Fe3O4 composites deposited on glassy carbon electrodes (GCEs) and integrated onto a portable potentiostat, CheapStat was developed. Characterization of the metal oxides through XRD, FTIR, and Raman Spectroscopy confirmed successful synthesis of the metal oxides while SEM analysis indicated submicron morphology. Cyclic voltammetry also confirmed the presence of redox peaks associated with Fe and Cu valence changes. Sensing performance of the CuO/Fe3O4 modified GCEs was determined using CheapStat with subsequent data smoothing and peak measurement implemented using MatLab®. Square wave voltammetry (SWV) performed under experimental conditions that yield peak current values showed that the sensor platform has a linear detection range from 0 ppm to 25 ppm. The sensitivity and limit of detection were also determined to be equivalent to -0.203±0.018 µA ppm-1 and 11.506±1.040 ppm, respectively. Evaluation of the sensor platform output in the presence of other chemical species and in spiked tap water samples indicate relatively moderate selectively. Overall, the results indicate the potential application of CuO/Fe3O4 based system for malathion detecti